Radiologic Outcomes Following All-Pedicle Screw Selective Thoracic Fusion in Adolescent Idiopathic Scoliosis Patients With Lenke Type 1 and 2 Curves - Shun Herng Tan; Chris Yin Wei Chan; Chee Kidd Chiu; Mohd Shahnaz Hassan; Mun Keong Kwan (Clinical Spine Surgery, 2026)
Study design: Retrospective study. Objective: To evaluate the long-term clinical and radiologic outcomes of adolescent idiopathic scoliosis (AIS) patients with Lenke 1B, 1C, 2B, and 2C curves treated with selective thoracic fusion (STF) using an all-pedicle screw construct. Summary of Background Data: STF has been reported in the literature to achieve better perioperative outcomes, including shorter operative duration, reduced blood loss, and lower operative risks. However, complications such as coronal decompensation (CD) and the adding-on (AO) phenomenon persist, even with strict selection criteria. Long-term data on the outcomes of STF using all-pedicle screw constructs remain limited. Methods: This retrospective study included 59 AIS patients who underwent single-staged posterior spinal fusion with an all-pedicle screw construct, with a minimum follow-up of 5 years. Radiologic outcomes and SRS-22r scores were analyzed. Complications, including AO, CD, lumbar decompensation (LD), and junctional kyphosis, were assessed. Results: At a mean follow-up of 5.8 years, the main thoracic (MT) curve correction was 60.3%. Spontaneous lumbar curve correction improved from 49.9% immediately postoperatively to 53.5% at the final follow-up ( P =0.046). Coronal balance (CB) shifted significantly from 1.8±12.7 mm preoperatively to −6.9±9.9 mm at the final follow-up ( P